Workplace violence among Pennsylvania education workers: Differences among occupations() - Tiesman, Hope (J Safety Res, 2012)
PROBLEM: The purpose of this study was to measure the prevalence and characteristics of physical and non-physical WPV in a state-based cohort of education workers. METHOD: A sample of 6,450 workers was drawn using de-identified union membership lists, stratified on gender, occupation, and school location. A cross-sectional survey was mailed to participants. RESULTS: An estimated 7.8% (95%CI = 6.6–9.1) of education workers were physically assaulted and 28.9% (95%CI = 26.4–31.5) experienced a non-physical WPV event during the 2009–2010 school year. Special education teachers were significantly more likely to be physically assaulted and experience a non-physical WPV event compared to general education teachers (Prevalence Rate Ratio = 3.6, 95% 2.4–5.5; PRR = 1.4, 95%CI = 1.1–1.8). DISCUSSION: Special education teachers were at the highest risk for both physical and non-physical WPV. If not already present, schools should consider implementing comprehensive WPV prevention programs for their employees. IMPACT ON INDUSTRY: Special education teachers have unique workplace hazards. Strategies that protect the special education teacher, while still protecting the special education student should be considered.